Factors Affecting the Assessment of Student Achievement - Wilson, Robert J.; Martinussen, Rhonda L. (Alberta Journal of Educational Research, 1999)
To what extent do expectations, disconfirming information, and degree of parental involvement in schooling affect teachers' judgments about a student's growth and achievement? This study manipulated these variables with 147 preservice teacher candidates as they assessed the progress of a student named Chris in language arts over a 10-week period. As predicted by social cognition findings, these results showed that early expectations and differential growth patterns were substantial contributors to differences in this student's reported final grade. For example, these assessors were impressed by their student's socioeconomic background and other contextual data, and this early information affected the grade awarded him or her weeks later. In addition, the pattern of achievement exhibited by Chris was also significantly related to the report card grade. If Chris seemed to improve, the grade improved, but if he or she remained steady or even fell behind, the grade was unaffected. The implications of these findings for assessment practice are discussed briefly in the conclusion.